Hubungan Social Media Addiction Instagram terhadap Indeks Prestasi Kumulatif pada Mahasiswa Program Studi Diploma Tiga Keperawatan Abulyatama - Meilisa Meilisa; Syukriadi Syukriadi; Ellyza Fazlylawati (Inovasi Kesehatan Global, 2025)
The prevalence of social media addiction is continuously increasing worldwide, including in Indonesia. Instagram has become the most widely used platform among students aged 18–25 years. Although Instagram provides many benefits, spending too much time on the application can cause learning concentration problems, procrastination, and a decrease in Grade Point Average (GPA). The purpose of this study was to determine whether there is a correlation between Instagram social media addiction and GPA among students of the Diploma Three Nursing Program at Universitas Abulyatama. This study applied a cross-sectional quantitative correlational design. The sampling technique used proportional random sampling, involving 78 students from a total population of 362 students. The research instruments consisted of cumulative GPA data and The Instagram Addiction Scale (TIAS). The study was conducted at the Diploma Three Nursing Program of Universitas Abulyatama from April 26 to May 9, 2025. Data analysis was performed using bivariate analysis with the Chi-Square test. The results showed that the majority of respondents were in the moderate category of Instagram addiction (56 students, 71.8%), followed by the high category (22 students, 28.2%). Meanwhile, GPA distribution indicated that 35 students (44.9%) were in the very high category, 24 students (30.8%) in the high category, and 19 students (24.3%) in the moderate category. The bivariate analysis with the Chi-Square test obtained a p-value of 0.001 (≤ 0.05), indicating a significant relationship between Instagram addiction and GPA. In conclusion, there is a correlation between Instagram social media addiction and students’ academic performance. Although Instagram use is widespread, students are expected to develop good time management skills and prioritize academic responsibilities to minimize the negative impact of social media use.